ANALYSIS OF THE EFFECT OF TEMPERATURE ON THE PHYSICAL PROPERTIES OF CATALYTIC CRACKING OF COCONUT OIL MICROEMULSION BIODIESEL - Paepenan, Semuel Poumer; Hamidi, Nurkholis; Purnami, Purnami; Anggara, Teuku (International Journal of Mechanical Engineering Technologies and Applications, 2026)
This study aims to analyze the effect of catalytic cracking temperature variation on the physical properties of coconut oil-based microemulsion biodiesel using a zeolite catalyst. The microemulsion biodiesel was produced by mixing coconut oil, ethanol, and butanol, followed by catalytic cracking treatment at temperatures of 50°C, 75°C, 95°C, 125°C, and 150°C. The key parameters observed included viscosity, density, flash point, calorific value, and cetane number. The results showed that increasing the catalytic cracking temperature led to a decrease in viscosity from 15.24 stokes in its initial state to 10.48 stokes at 150°C, indicating the breakdown of heavy molecules into lighter fractions. Density fluctuated, reaching its highest value of 0.879 g/cm³ at 75°C before stabilizing at approximately 0.878 g/cm³ at 150°C. The flash point exhibited a non-linear trend, peaking at 30.5°C at 75°C before decreasing again. The calorific value increased significantly from 8769.70 cal/gram to 9342.93 cal/gram at 150°C, demonstrating an enhancement in the energy content of the biodiesel. Meanwhile, the cetane number was recorded at 75 at both 95°C and 150°C, indicating good combustion quality. Based on these findings, the optimal catalytic cracking temperature was determined to be 150°C, yielding biodiesel with lower viscosity, higher calorific value, and improved combustion performance. This study demonstrates that catalytic cracking can enhance the quality of microemulsion biodiesel, with further optimization potential for industrial-scale applications.